ANALISIS PENGARUH KONDISI SOSIAL EKONOMI TERHADAP KEPUTUSAN WANITA MENJADI PEKERJA SEKS - Aryawan, Shinta Dewi; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study is; 1) to analyze the simultaneous effect of education levels, job skills, social networks, income, and family support on women's decisions to become sex workers; 2) to analyze the partial effect of education levels, job skills, social networks, income, and family support on women's decisions to become sex workers; 3) to analyze the role of family support in moderating the effect of income on a woman's decision to become a sex workers. The analytical technique used in this study is Moderation Regression Analysis (MRA). The results of this study indicate that; 1) education level, job skills, social network, income, and family support simultaneously affects on a woman's decision to become a sex worker; 2) the level of education and employment skills negatively affects the decision of women to become sex workers; 3) social networks, income, and family support have a positive effect on women's decisions to become sex workers. 4) family support moderates the influence of income on women's decisions to become sex workers.